Actuation and biomedical development of micro-/nanorobots – A review. (June 2022) - Zhao, S.; Sun, D.; Zhang, J.; Lu, H.; Wang, Y.; Xiong, R.; Grattan, K.T.V.
Abstract: Over the past 20 years, there has been considerable progress in the development of research in the micro-/nanorobotics area. Through major, rapid, investment in the field and the use of, for example, correlation techniques, many successes have been seen in both theoretical and experimental work, which have had applications in emerging areas such as clinical medicine. As a result, this article aims to introduce and review some of the most influential and advanced research work carried out over the past few years. To do so, the approach taken has been to categorize micro-/nanorobots by their propulsion modes, analyzing their advantages and drawbacks in detail, looking at medical applications such as such as the delivery of medical supplies, medical imaging and so on. Additionally, the article looks at future directions in micro-/nanorobot development, including important areas such as biocompatibility (as well as biodegradability), autonomy and accurate operation in the complex and dynamic environment of the human body. Graphical abstract: Image 1 Highlight: This review manages the actuation and application of micro-/nanorobots. The most influential and advanced micro-/nanorobots carried out over the past few years have been discussed in detail. Typical works are categorized by their propulsion modes, analyzing their advantages and drawbacks in detail, looking at medical applications. The difficulties and future directions for the practical use of micro-/nanorobots in the biomedical fields are discussed.